High-performance large-area perovskite photovoltaic modules - Chu, Liang; Zhai, Shuaibo; Ahmad, Waqar; Zhang, Jing; Zang, Yue; Yan, Wensheng; Li, Yongfang (Nano Research Energy, 2022)
Perovskite solar cells (Pero-SCs) exhibited a bright future for the next generation of photovoltaic technology because of their high power conversion efficiency (PCE), low cost, and simple solution process. The certified laboratory-scale PCE has reached 25.7% referred to small scale (2) of Pero-SCs. However, with the increase of the area to module scale, the PCE drops dramatically mainly due to the inadequate regulation of growing large-area perovskite films. Therefore, there is a dire need to produce high-quality perovskite films for large-area photovoltaic modules. Herein, we summarize the recent advances in perovskite photovoltaic modules (PPMs) with particular attention paid to the coating methods, as well as the growth regulation of the high-quality and large-area perovskite films. Furthermore, this study encompasses future development directions and prospects for PPMs.